BIOOEGRAOASI SENYAWA AROMATIK OLEH PSEUDOMONAS SP ISOLAT I4 DARI TABLET BAKTERI - T. Sembiring; Lies Sriwuryandari (Jurnal Kimia Terapan Indonesia, 2000)
Biodegradation test of aromatic compounds by pure cultureof bacterial isolate I4 from bacterial tablet using mineral mediumas growth medium was done. Aromatic compounds tested ascarbon sources used were phenol, p-chlorphenol, p-nitrophenol,2,4 dichlorphenol and benzene. The oval colony forming and highmotility isolate is an aerobic and gram negatif bacteria. Theisolate was able to use citric acid as carbon source, producedacid .from methyl red test and gave negative result of indol test.The isolate formed a slightly blue-green colour colony on agarslant, and it did not use ethanol as carbon source. Thecharacteristic of the isolate I4 indicated that it belonged to thegenus Pseudomonas. Test using selective media confirmed thatthe isolate I4 is a Pseudomonas fluorescence. The capability ofthe bacteria to oxidize of 2,4 dichlorphenol was relatively fast.Experimental results showed that the bacteri grew on benzene atconcentration of 10% (v/v), and degraded 2,4 dichlophenol withrelatively high rate.Keywords: Bacterial tablet, aromatic compounds, phenol. pchlorphenol,2,4 dichlorphenol, p-nitrophenol, benzene, pure culture,Pseudomonas fluorescence, isolate I4